International Human Rights Standards And The Practice Of Ensuring The Right To Protection From Criminal Prosecution In Russia And Some Foreign Countries. - ALEXANDROVA ОLGA PAVLOVNA; BUDANOVA, LYUDMILA YURYEVNA; SMIRNOVA, IRINA NIKOLAEVNA; KOZAK, BRONISLAV BRONISLAVOVICH; NIKOLAEVICH, MATVEEV DMITRY (The journal of contemporary issues in business and government, 2021)
The protection of the rights and freedoms of persons subject to criminal prosecution, participation of counsel in criminal proceedings are always the center of attention of the progressive world community and legislators. However, the practice of ensuring the right to protection of persons from suspicion or accusation in some countries, including taking into account the decisions of the European Court of Human Rights, indicates that not all issues of its legal regulation have been resolved to a degree that satisfies science and practice, and there are violations of human rights enshrined in international legal standards, the principle of adversarial parties in criminal proceedings is not fully implemented, so there is increasing scientific interest in problematic issues of protection from criminal prosecution. Despite the great contribution of the conducted research to the development of the institute of protection from criminal prosecution, many issues related to the implementation of international standards in the field of human rights in the provision of this protection in the criminal proceedings of Russia and some foreign countries have not been fully covered and require a comprehensive study. The purpose of the study is to analyze international standards in the field of human rights, as well as the experience of Russia and some foreign countries in the field of ensuring the right to protection from criminal prosecution in criminal proceedings, to identify problematic issues of a legal nature in this part and to formulate scientifically based recommendations for their solution (minimization).